Wykonaj mnożenie i zredukuj wyrazy podobne
A. (x+3)(x²-1)
B. (a-6)(3+a)
C. (2x-3)(1-4x)
D. (3a-1)(5a+1)


Odpowiedź :

A.

[tex](x + 3)( {x}^{2} - 1) = {x}^{3} - x + 3 {x}^{2} - 3 [/tex]

B.

[tex](a - 6)(3 + a) = 3a + {a}^{2} - 18 - 6a = {a}^{2} - 3a - 18[/tex]

C.

[tex](2x - 3)(1 - 4x) = 2x - 8 {x}^{2} - 3 + 12x = - 8 {x}^{2} + 14x - 3[/tex]

D.

[tex](3a - 1)(5a + 1) = 15 {a}^{2} + 3a - 5a - 1 = 15 {a}^{2} - 2a - 1[/tex]

Odpowiedź:

A. (x+3)(x²-1)=x³-x+3x²-3=x³+3x²-x-3

B.(a-6)(3+a)=3a+a²-18-6a=a²-3a-18

C. (2x-3)(1-4x)=2x-8x²-3+12x=-8x²+14x-3

D.(3a-1)(5a+1)=15a²+3a-5a-1=15a²-2a-1

Szczegółowe wyjaśnienie: